Real “Time Entry and Display of Clinical Data in an Intensive Care Unit) - JOLY, H.; TROTTER, J.; WEIL, M. H.; SHUBIN, H. (Methods of Information in Medicine, 1971)
A system for entry, storage and retrieval of textual information on the patient’s history and physical examination, as well as the physician’s progress notes, has been designed for use in a critical care environment: The system, which utilizes a digital computer, concurrently monitors signals from sensors measuring physiological parameters.Textual information on the history and physical examination is entered into the computer by the physician or nurse using a bedside terminal. Coded formats are used to enter the data. Provision is also made for entry of comments in natural language and for formal structuring of answers by the use of selected comments from lists of answers. The information is stored on a disk as textual summaries which are interwoven with analog summaries.Data on current patients, or on previous patients, are displayed on the terminal on request of the physician. This method of handling textual information provides a practical means of acquiring detailed clinical data and correlating it with physiological measurements, thereby facilitating rapid interpretation of changes in the status of the critically ill patient.
Keywords: Intensive Care Unit; On-Line Data Processing; Processing of Textual Information; Patient Monitoring